2013
DOI: 10.5539/ass.v9n12p125
|View full text |Cite
|
Sign up to set email alerts
|

Integration of National Character Education and Social Conflict Resolution through Traditional Culture: A Case Study in South Sumatra Indonesia

Abstract: Local wisdom is related to the community’s ability to understand the surrounding condition and the environment, which then is adapted to the existing situation. Local wisdom contributes to the way of living, knowledge and life strategies in the form of actions done by the local community to respond to various problems and meet their needs in life. Each community has its own outlook about a conflict that it is facing. The outlook is very dependent on the general conceptual framework, or a culture that surround … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…For that reason, instrumental efforts must be created to improve the effectiveness of the learning process along with positive cultural and character development and can avoid conflict among fellow students in the classroom (Alfitri & Hambali, 2013). Thus, character integration in learning is one of the interventions planned to help individuals through dynamic interpersonal processes oriented towards prevention and development (Berkowitz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, instrumental efforts must be created to improve the effectiveness of the learning process along with positive cultural and character development and can avoid conflict among fellow students in the classroom (Alfitri & Hambali, 2013). Thus, character integration in learning is one of the interventions planned to help individuals through dynamic interpersonal processes oriented towards prevention and development (Berkowitz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The values of character education that are contained in the education curriculum in Indonesia are reflected from the values of local community wisdom (Anggraini & Kusniarti, 2017;Hidayati et al, 2020;Rasna & Tantra, 2017;Sugiyo & Purwastuti, 2017;Suhartini et al, 2019). Many studies have raised the issue of strengthening character by integrating local traditional values into learning such as traditional games, teachings, and philosophy (Alfitri & Hambali, 2013;Sukendar et al, 2019;Supeni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, Indonesia has a diversity of wisdoms as a social capital that contributes positively to both violence prevention and conflict resolution. These include the "Muakhi" tradition in Lampung (Hartoyo, 2019), the "Pela Gandong" tradition in Maluku (Bakri, 2015) and the "Tepung Tawar" tradition in South Sumatra (Alfitri and Hambali, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These problems have remained within the community in spite of the various resolution efforts. Sociologically, a number of previous studies showed the complexity of the relationships among those variables (Alfitri and Hambali, 2013;Allen and Barter, 2016;Mavridis, 2015;Roth and Sumarto, 2015).…”
Section: Introductionmentioning
confidence: 99%